Prácticas de seguridad y salud en obras de pistas y veredas en la prevención de accidentes laborales. Iquitos, 2024 - Silva Jarama, Diego Marcelo (2024)
The study evaluated the procedures to reduce workplace accidents in civil works on tracks and sidewalks at the AAHH Francisco Secada Vignetta, San Juan Bautista. With a sample of 50 workers and safety managers, a structured questionnaire (Cronbach's Alpha: 0.790) and non-parametric tests (Shapiro-Wilk and Rho Spearman) were used. The results revealed high physical and chemical risks perceived by workers, highlighting the need for personal protective equipment and adequate ventilation systems. Occupational safety training was identified as essential, although with gaps in its implementation. In addition, necessary improvements were detected in communication and clarity of procedures, essential to prevent accidents. The impact of psychosocial factors, such as stress and workplace harassment, on workers' well-being was also evident, suggesting the need for clear policies and psychological support. On the other hand, a favorable disposition of workers to participate in intervention programs was observed. Finally, it was concluded that there is a strong positive correlation between the evaluation of safety measures and the evaluation of the intervention program, showing that these strategies contribute significantly to the reduction of workplace accidents.